Optimization of Production Scheduling and Planning of Raw Materials Supply Using Markov Chains (A Case Study of Kinken Cake & Bakery Kutoarjo) - Oktaviyani, Oktaviyani; Dwijanto, Dwijanto; Supriyono, Supriyono (Unnes Journal of Mathematics, 2018)
Competition in the industry sector influences the companies to increase productivity in their production activities, such as production scheduling. Production scheduling consists of various aspects, those are amount of production, production costs, and the availability of raw materials production. The scope of operations research used in this study was Markov chains. The decision process was used in order to decide the amount of production demand, planning of raw material supply of Kinken products Cake & Bakery Kutoarjo. . The problem was how to use Markov chains in production scheduling and planning of bread raw materials, how was the optimal policy in planning raw materials supply by considering its scheduling production. This study aimed at finding out Markov chains steps to estimate the amount of products demand for the upcoming time period in order to obtain production scheduling and planning of bread raw materials, and to obtain the optimal policy in planning of raw material supply Results showed that a market share of total demand products every the upcoming two weeks period, the equilibrium market share in the 59th week period got production demand 0.7% of bread brownies, 12.7% of Nastro rolls bread, 63.1%, of Spc rolls bread, 2.6% Bansos rolls bread, and 22.3% of semicircle spongecake, meanwhile the optimal policy in planning of raw material supply was seen from the percentage of production demand those bread. The raw materials supply of flour, sugar, and eggs was saved 63.1% for (1) the Spc rolls production, (2) the semicircle spongecake, (3) the Nastro rolls, (4) the 2.6% for Bansos rolls, and (5) 0.7% for the brownies bread.